Perception of drug abuse in society: a scale development study - Polat, Hakkı; Kök, Bayram (Journal of Dependence, 2019)
Objective: The aim of this study is to develop a scale upon perception of drug abuse in society.Method: The study sample consisted of a total of 1531 person aged over 18 years old. For this sampling, a few district were selected randomly in Eskişehir. There have been obtained data for demographic properties and perception of drug abuse by the surveys which applied to persons. Existing perception of drug abuse in society has been researched by the analyzing the collected data.Results: There is four important factor up to begin drugs and continue to drug abuse: personal conditions by family attitude, society and friends, society susceptibility and the struggle of institutions and organizations. The reliability of these 4 factors was 84,8%, the variance explanation rate was 52% and the goodness of fit values were higher than 90%.Conclusion: People think that family, friendship, society and institutions are effect up to starting drugs abuse. However, they are refraining from expressing a role to themselves in the struggle against this problem too. People are considered to be responsible for this subject, but people also think that they exclude the drug addicts and their family.
Keywords: Drug abuse; social conditions; social behavior disorder